Analisis of structure of the railways flora within the Belgorod city territories - Тохтарь, В. К.; Фоміна, О. В.; Ковальчук, І. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
Analisis of the railways flora formation in Belgorod city agglomeration has been conducted. 283 species, most of which are represented as native plants have been revealed based on a critical analysis of structures of the flora studied. Assessment of immigration modes and naturalization degree of the invasive species has been made. Assumptions about the high probability of new invasive species appearance in this type of ecotope have been disscussed.